Outcome of the antiretroviral treatment intervention in Mankweng - Ledwaba, Ramatsobane Johanna (My University, 2016)
The purpose of this research was to assess outcomes of the antiretroviral treatment intervention in Mankweng. The antiretroviral treatment intervention was conceived with the aim to reduce HIV transmission through viral load suppression. Literature has shown that viral load is used as a tool to measure the performance of the intervention and studies on viral load outcomes in rural settings of Limpopo are limited. For this reason, the research was focused on viral load suppression with the aim of (1) determining the proportion of adults with viral load suppression among people taking antiretroviral treatment for 12 months, and (2) identifying factors associated with failure to achieve viral load suppression among people on antiretroviral treatment for 12 months. Binomial logistic regression model was used to identify factors associated with failure to suppress viral load. This study used the theory of change to interpret its findings as well as theories of behavioural planning and self-regulation models to understand the logic that underpins the theory of change. The findings revealed that the majority (78%) of adults achieved viral load suppression, and a quarter of the individuals failed to suppress the viral load. There was no significant difference in baseline characteristics between people who achieved viral load suppression and those who did not. In addition, males, with a low CD4 and opportunistic illnesses when in the primary disease stages were more likely to fail to suppress the viral load. Moreover, people who were initiated on a 3-pill containing treatment and do not have social support were also likely to fail to achieve viral load suppression. Although the study showed a trend of likelihood towards failure to achieve viral load suppression, the estimates were not statistically significant. Theoretical arguments from this study suggest that failure to achieve viral load was attributed to poor adherence to treatment. This is supported by the logic that underpins the theory of change, in which the assumption of adherence was possibly violated. However, the results chain framework highlighted that the implementation of the intervention was effective as it led to good outcomes and an effective intervention. Drawing all this together, the study highlights the need for intensified adherence counseling during treatment in order to improve the performance of the intervention. Author: Ramatsobane Johanna Ledwaba, Thesis Title: Outcomes of the antiretroviral treatment intervention in Mankweng, Johannesburg, March 2016
Thesis presented in partial fulfilment for the degree of Master of Management (in the field of Public Sector Monitoring and Evaluation) to the Faculty of Commerce, Law, and Management, University of the Witwatersrand 2016
Keywords: AIDS (Disease)--Treatment--South Africa; HIV infections--Treatment--South Africa; HIV-positive persons--Treatment--South Africa; Antiretroviral agents--South Africa